2009
DOI: 10.1007/s10298-009-0517-1
|View full text |Cite
|
Sign up to set email alerts
|

Effet antihypertenseur des feuilles d’Inula viscosa

Abstract: L'effet antihypertenseur de l'extrait aqueux (EA) des feuilles d'Inula viscosa a été évalué sur des rats rendus hypertendus par un traitement au L-NAME (NG-nitro-Larginine méthyle ester). L'évolution de la pression artérielle est évaluée en mesurant la pression artérielle systolique (PAS) à l'aide d'un plétysmographe. Nos investigations ont porté sur trois groupes de rats : un groupe témoin, un groupe traité au L-NAME (30 mg/kg par jour) et un groupe traité au L-NAME (30 mg/kg par jour) et à l'EA d'Inula visco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…I. viscosa root and leaf decoctions have been used as useful and precious remedies for hypertension, diabetes mellitus and cardiac diseases [ 9 , 10 ]. Several recent experimental works have shown that extract of I. viscosa possess antifungal [ 11 ], antibacterial [ 12 ], hypoglycemic [ 13 ], antihypertensive [ 14 ], antiproliferative [ 15 ], anti-inflammatory [ 16 ] and strong antioxidant activity [ 17 , 18 ]. In addition, numerous secondary metabolites, isolated from Inula species, have shown their effectiveness against oxidative stress related diseases (cancer, diabetes and inflammation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…I. viscosa root and leaf decoctions have been used as useful and precious remedies for hypertension, diabetes mellitus and cardiac diseases [ 9 , 10 ]. Several recent experimental works have shown that extract of I. viscosa possess antifungal [ 11 ], antibacterial [ 12 ], hypoglycemic [ 13 ], antihypertensive [ 14 ], antiproliferative [ 15 ], anti-inflammatory [ 16 ] and strong antioxidant activity [ 17 , 18 ]. In addition, numerous secondary metabolites, isolated from Inula species, have shown their effectiveness against oxidative stress related diseases (cancer, diabetes and inflammation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This taxonomic change is confirmed in the online "The Plant List" database. It should also be noted that the name I. viscosa continues to appear in the literature (Kattouf et al 2009;Talib et al 2012;Andolfi et al 2013;Haoui et al 2015;Prisa 2019).…”
Section: Introductionmentioning
confidence: 99%
“…for a long time(Cafarchia et al 2002;Kattouf et al 2009). D. viscosa is known for its antihypertensive(Kattouf et al 2009), anti-in ammatory and antioxidant(Lounis et al 2009), antidiabetic, antipyretic, wound healing, antiseptic and antiphlogistic activities (Lauro and Rolih 1990; Omezzine et al 2011) and its antiulcerogenic action is attributed to its avonic composition.…”
mentioning
confidence: 99%
“…for a long time(Cafarchia et al 2002;Kattouf et al 2009). D. viscosa is known for its antihypertensive(Kattouf et al 2009), anti-in ammatory and antioxidant(Lounis et al 2009), antidiabetic, antipyretic, wound healing, antiseptic and antiphlogistic activities (Lauro and Rolih 1990; Omezzine et al 2011) and its antiulcerogenic action is attributed to its avonic composition. Moreover, extracts of D. viscosa were tested for thier antiviral(Abad et al 2000), antifungal(Mamoci et al 2011), antimicrobial(Maoz and Neeman, 1998), antibacterial(Squalli et al 2007), herbicidal(Muehlchen et al 1990) nematicidal(Oka et al 2006), acaricidal(Mansour et al 2004) and insecticidal activities(Alexenizer and Dorn 2007).…”
mentioning
confidence: 99%